USE OF COMPUTER MODELS IN THE EDUCATIONAL PROCESS AND DEVELOPMENT OF STUDENTS' CREATIVE THINKING (TAMADDUN NURI JURNALI, 2024)
This article presents the method of developing students' creative thinking through the use of computer models in the educational process. The use of computer models is shown in the example of the laboratory exercise on the topic "Determining the wavelength of light using a diffraction grating".